Ef fect of Physical Elicitation on Arachis hypogaea Seeds on the Agronomic Behavior of the Crop - Joya-Dávila, José Gregorio; Gutiérrez-Miceli, Federico Antonio; Oliva-Llaven, María Ángela; Santos-Espinoza, Ana Martin (REVISTA TERRA LATINOAMERICANA, 2025)
Peanut (Arachis hypogaea) is a crop of great importance in human nutrition and in national and international markets, thanks to its rich nutrient profile and versatile applications in both gastronomy and the cosmetics industry. However, peanut production faces challenges such as drought and phytopathogen control. In this context, this study evaluated the impact of laser irradiation, magnetic fields, and UV-C light on agronomic variables of peanut. An experimental design of completely randomized blocks was used, with four treatments and three replicates each, measuring 41 variables, from germination to morphometric and yield characteristics. The results showed that laser irradiation increased seed biomass, while UV-C light increased the production of pods with three seeds. Surprisingly, the magnetic field resulted in the highest yield in pods, hulls, and seeds, with an 80% increase in production per hectare, especially under drought conditions. These results suggest that physical stimuli could be a valuable alternative to improve peanut yield under unfavorable climatic conditions, of fering new perspectives for both agronomic research and field practice, highlighting the importance of exploring and better understanding the role of these stimuli in enhancing crop performance and food security.